Hydrate Inhibition with PEO (Poly 2-ethyl-2-oxazoline) - Bulbul, S.; Kadoura, A. S.; Merey, S.; Parlaktuna, Mahmut (Energy Sources, Part A: Recovery, Utilization, and Environmental Effects, 2014)
This study is aimed at investigating the effects of a poly 2-ethyl-2-oxazoline-type polymer on the prevention of methane hydrate formation. During the study, seven experiments with low concentrations of poly 2-ethyl-2-oxazoline (0 to 1 wt%) were run in a batch-type reactor. The analysis of the experimental study indicates that poly 2-ethyl-2-oxazoline can be considered as a potential kinetic inhibitor for hydrate formation.